A new responder criterion (relative effect per patient (REPP) >0.2) externally validated in a large total hip replacement multicenter cohort (EUROHIP) - Huber, J; Hüsler, J; Dieppe, P; Günther, K; Dreinhöfer, K; Judge, A (Elsevier, 2015)
Objective: To validate a new method to identify responders (relative effect per patient (REPP) >0.2) using the OMERACT-OARSI criteria as gold standard in a large multicentre sample. Method: The REPP ([score before – after treatment]/score before treatment) was calculated for 845 patients of a large multicenter European cohort study for THR. The patients with a REPP >0.2 were defined as responders. The responder rate was compared to the gold standard (OMERACT-OARSI criteria) using receiver operator characteristic (ROC) curve analysis for sensitivity, specificity and percentage of appropriately classified patients. Results: With the criterion REPP>0.2 85.4% of the patients were classified as responders, applying the OARSI-OMERACT criteria 85.7%. The new method had 98.8% sensitivity, 94.2% specificity and 98.1% of the patients were correctly classified compared to the gold standard. Conclusion: The external validation showed a high sensitivity and also specificity of a new criterion to identify a responder compared to the gold standard method. It is simple and has no uncertainties due to a single classification criterion.